2023
DOI: 10.1371/journal.pgph.0000904
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nursing mothers’ knowledge, perceptions and uptake of Sulphadoxine Pyrimethamine (IPTp-SP) during pregnancy in the Ho Teaching Hospital of the Volta Region of Ghana

Abstract: Intermittent preventive therapy during pregnancy with Sulphadoxine Pyrimethamine (IPTp-SP) is one of the potent strategies for preventing malaria in pregnancy (MiP). Factors such as the pregnant woman’s knowledge and very importantly perception or belief about IPTp-SP remains key determinant of IPTp-SP uptake. This study assessed the knowledge and perception of nursing mothers and their uptake of IPTp-SP during pregnancy in the Ho Teaching Hospital. We administered a close-ended questionnaire to 303 nursing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Assessing the knowledge of respondents on IPTp, this study found that 187 (100%) pregnant women had ever heard of IPTp. Similarly, a study conducted in the Volta Region, Ghana, also found that approximately 265 (87.5%) pregnant women had heard of IPTp [27]. The majority (177, 94.7%) correctly knew that IPTp-SP was a drug for preventing malaria in pregnancy, and this finding was similar to a study conducted in the Volta Region of Ghana and Tanzania, which found that more pregnant women reported that the drug prevents malaria in pregnancy [28,29].…”
Section: First Anc Visit Period Of Iptp-sp Initiation and Therapeutic...supporting
confidence: 62%
“…Assessing the knowledge of respondents on IPTp, this study found that 187 (100%) pregnant women had ever heard of IPTp. Similarly, a study conducted in the Volta Region, Ghana, also found that approximately 265 (87.5%) pregnant women had heard of IPTp [27]. The majority (177, 94.7%) correctly knew that IPTp-SP was a drug for preventing malaria in pregnancy, and this finding was similar to a study conducted in the Volta Region of Ghana and Tanzania, which found that more pregnant women reported that the drug prevents malaria in pregnancy [28,29].…”
Section: First Anc Visit Period Of Iptp-sp Initiation and Therapeutic...supporting
confidence: 62%
“…The uptake of optimal doses in the current study far exceeds the 64.5% and 71.0% reported in some Ghanaian studies 26,40 but comparable to the 2019 report of 80.7% in Sekondi-Tarkoradi also in Ghana. 24 It is, however, lower than the 95% reported among post-partum women about a year earlier at the same study site 32 and this calls for operational research into the seeming reduction in uptake of optimal IPTp-SP doses at HTH. Age >25 years, employment and good knowledge of MiP facilitated uptake of optimal IPTp-SP doses while starting ANC later than 13 weeks was a barrier.…”
Section: Discussionmentioning
confidence: 85%
“…Literature review showed two studies that reported on uptake of either ITNs or IPTp-SP but not both in the Ho Municipality. 28,32 A 42.5% ITN utilization was reported among antenatal care (ANC) attendants in the municipality in 2016 with higher educational level being a significant facilitator 28 while the second study found that 95% of post-partum women received 3–5 doses of IPTp-SP in 2021. 32 The present study was conducted among post-natal care (PNC) attendants at the Ho Teaching Hospital (HTH) to primarily assess current uptake of the two MiP interventions and the factors influencing them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation